The New Woman Avatar in Chetan Bhagat’s One Indian Girl - Baral, Pawan (Pursuits: A Journal of English Studies, 2024)
The paper aims at exploring the female protagonist, Radhika Mehta, of One Indian Girl by Chetan Bhagat in the light of the ideals of the New Woman in Indian context. This is an ideal which had emerged in the late 19th century and has had a profound influence to date. It associates women as independent, physically adept and mentally acute, and able to work, study, and socialize equal to men. Having been exposed to many Western countries during her career, Radhika focuses on her status and career, earns more than boys normally does, involves in premarital sex, and shows her individuality. However, she cannot renegotiate the traditional roles altogether. Rather, she tries to evade a critique of power relations within the family and attempt to get the best of both worlds, concretizing existing gender roles and taking on additional new ones.